The Effect of Ethanolic Extract from Moringa oleifera Leaves in Collagen Density and Numbers of New Capillary Vessel Count on Wistar Rats Burn Wound - Supandi Andy; Najatullah; Nugroho Trilaksana; Neni Susilaningsih (HM Publisher, 2022)
Background: Burns are a major cause of morbidity, including prolonged length of stay and disability, which requires no small amount of treatment costs. Currently, there are many studies to accelerate the healing of wounds, one of which is with Moringa oleifera (MO). This study aimed to prove the effect of ethanolic extract from MO leaves on collagen density and new capillary vessel count on Wistar rats' burn wounds. Methods: This research is randomized post-test only with a control group design. Twenty-four male Wistar rats induced burn wounds and were randomly divided into 4 groups which were given topical medicine once daily for 10 days; P1 (MO leaves extract 10%), P2 (Silver Sulfadiazine + MO leaves extract 10%), P3 (SSD), and P4 (negative control). Collagen density was assessed using the Kruskal-Wallis test and continued with Mann-Whitney Test. New capillary vessel count was assessed using Hematoxylin-Eosin staining and One Way ANOVA. The correlation test between two variables was tested using the Spearman test. Results: Collagen Density shows significant difference in group P1 compared to P4 (p=0,016), group P2 compared to P3 (p=0,047), group P2 compared to P4 (p=0,009). A significant increase in new capillary blood vessel counts was seen in group P1 compared to P3 and P4 (p=0.001; 0,000) and group P2 compared to P3 and P4 (p=0,000;0,000). A positive correlation was found between the new capillary blood vessel count and epithelization percentage (p=0,001), with a strong correlation (rho=0,682). Conclusion: Ethanolic extract from Moringa oleifera leaves proved to be effective in increasing collagen density and new capillary vessel count.